A case of vascular Behçet's disease complicated with acute myocardial infarction due to spontaneous coronary artery dissection. Issue 4 (October 2020) - Hitomi, Yasuhiro; Numasawa, Yohei; Yamanaka, Shinsuke; Fujita, Hiroshi; Fujita, Yoko; Tomimatsu, Souichi
Abstract: Spontaneous coronary artery dissection (SCAD) is a rare cause of acute myocardial infarction and occurs predominantly in young women without conventional cardiovascular risk factors. Emotional or physical stress and hormone imbalance are associated with the occurrence of SCAD, but the precise mechanisms have not been sufficiently elucidated. Furthermore, there is a paucity of data regarding the underlying disease in patients with SCAD. We herein report a case involving a 48-year-old man who developed acute myocardial infarction due to SCAD in the distal segment of the left anterior descending artery and was successfully treated with conservative medical therapy. A repeat coronary angiography examination performed 2 weeks later revealed complete angiographic healing. In addition, he was treated for suspected Behçet's disease because he had a history of recurrent aphthous stomatitis, nodular erythema, and genital ulcers. After thorough assessment, he was finally diagnosed with vascular Behçet's disease based on additional evidence of bilateral deep vein thrombosis. This case report highlights a rare case of vascular Behçet's disease complicated with SCAD in a male patient. Physicians should be aware that SCAD may occur in association with systemic inflammatory disease including Behçet's disease, even in male patients. <Learning objective: Spontaneous coronary artery dissection (SCAD) is a rare disease entity that can cause acute myocardial infarction especially in young individuals without significant cardiovascular risk factors. We herein describe a 48-year-old man who was diagnosed with vascular Behçet's disease after undergoing conservative medical therapy for acute myocardial infarction due to SCAD. This case report highlights that SCAD may occur in association with systemic inflammatory disease including Behçet's disease, even in male patients.>